Gastric volvulus and wandering spleen; a life-threatening surgical emergency - Mirza, Aazma; Khan, Naeem; Shahid, Ayesha; Khan, Kamran (Journal of the Pakistan Medical Association, 2022)
Wandering spleen and gastric volvulus are two of the rarely encountered conditions occurring together with or without other congenital and acquired defects. These potentially fatal conditions originate from a shared cause, i.e. the defect of intraperitoneal ligaments resulting in a failure to withhold these organs at their anatomical position and alignment. This can come to attention in both childhood and/or adulthood, and the diagnosis calls for a high degree of suspicion and a failure to diagnose can culminate in death of both the organs, i.e. the spleen and stomach. We are presenting the case of a 20-year-old girl who underwent an emergency laparotomy for gastric volvulus and wandering spleen. Keywords: Spleen, volvulus, surgery, torsion